40 YEARS OF EXISTENCE OF DEPARTMENT OF AGRICULTURAL EXTENSION AND RURAL SOCIOLOGY: SUCCESS AND PROBLEMS - FARINDE, A. J; JIBOWO, A. A.; OLAOGUN, E. A.; TORIMIRO, D. O.; ADERETI, E. O.; DEJI, O. F.; AJAYI, A. O.; KOLAWOLE, O. D.; AGBOOLA, A. F.; OGBINMI, G. E.; OGUNBA, B. O.; SOYEBO, K. O.; et al. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
No Abstract